Metal Transformation by a Novel Pelosinus Isolate From a Subsurface Environment - Ray, Allison E.; Connon, Stephanie A.; Neal, Andrew L.; Fujita, Yoshiko; Cummings, David E.; Ingram, Jani C.; Magnuson, Timothy S. (Frontiers in Microbiology, 2018)
The capability of microorganisms to alter metal speciation offers potential for the development of new strategies for immobilization of toxic metals in the environment. Pelosinus strain UFO1 was isolated under strictly anaerobic conditions from an Fe(III)-reducing enrichment established with uncontaminated soil from the Department of Energy Oak Ridge Field Research Center (ORFRC), Tennessee. Strain UFO1 is a rod-shaped, spore-forming, and Gram-variable anaerobe with a fermentative metabolism. It is capable of reducing the humic acid analog anthraquinone-2,6-disulfonate (AQDS) using a variety of fermentable substrates and H2. Reduction of Fe(III)-nitrilotriacetic acid occurred in the presence of lactate as carbon and electron donor. Ferrihydrite was not reduced in the absence of AQDS. Nearly complete reduction of 1, 3, and 5 ppm Cr(VI) occurred within 24 hours in suspensions containing 108 cells mL-1 when provided with 10 mM lactate; when 1 mM AQDS was added, 3 and 5 ppm Cr(VI) were reduced to 0.1 ppm within 2 hours. Strain UFO1 is a novel species within the recently described bacterial genus Pelosinus, having 98.16 % 16S rRNA gene sequence similarity with the most closely related described species, Pelosinus fermentans R7T. The G+C content of the genomic DNA was 38 mol %, and DNA-DNA hybridization of strain UFO1 against Pelosinus fermentans R7T indicated an average 16.8% DNA-DNA similarity. The unique phylogenetic, physiologic, and metal-transforming characteristics of strain UFO1 reveal it is a novel isolate of the described genus Pelosinus.